Efektifitas Strategi Pemasaran Digital melalui Media Sosial Studi pada Akun Instagram Mikhayla_shop - Aini, Saqofa Nabilah (Jurnal Manajemen dan Inovasi (MANOVA), 2024)
This study aims to analyze the form of digital marketing strategies through social media on Instagram accounts Mikhayla_shop and the effectiveness of digital marketing. So in this study, there are two formulations of the problem, namely: 1) How is digital marketing strategy through social media study on Instagram account Mikhayla_shop?; and 2) How effective is digital marketing through social media studies on Instagram account mikhayla_shop? This study uses qualitative research methods with a descriptive approach. Primary data sources come from interviews, observations, and document studies with owners and employees of the Mikhayla_shop. While the secondary data sources come from books, information sources and archives, and official personal documents. The data collection technique is done by structured interviews, indirect observation, and documentation related to sales data and strategy modes that have been carried out. The results showed that the digital marketing strategy through social media conducted by mikhayla_shop is quite effective and is based on segmentation, targeting, and positioning activities. The use of effective digital marketing strategies can attract more consumer buying interest and can increase sales.